Echinacea Purpurea For the Long-Term Prevention of Viral Respiratory Tract Infections During Covid-19 Pandemic: A Randomized, Open, Controlled, Exploratory Clinical Study - Kolev, Emil; Mircheva, Lilyana; Edwards, Michael R.; Johnston, Sebastian L.; Kalinov, Krassimir; Stange, Rainer; Gancitano, Giuseppe; Berghe, Wim Vanden; Kreft, Samo (Frontiers in Pharmacology, 2022)
SARS-CoV-2 vaccination is effective in preventing severe Covid-19, but efficacy in reducing viral load and transmission wanes over time. In addition, the emergence of novel SARS-CoV-2 variants increases the threat of uncontrolled dissemination and additional antiviral therapies are urgently needed for effective containment. In previous in vitro studies Echinacea purpurea demonstrated strong antiviral activity against enveloped viruses, including SARS-CoV-2. In this study, we examined the potential of Echinacea purpurea in preventing and treating respiratory tract infections (RTIs) and in particular, SARS-CoV-2 infections. 120 healthy volunteers (m,f, 18 – 75 years) were randomly assigned to Echinacea prevention or control group without any intervention. After a run-in week, participants went through 3 prevention cycles of 2, 2 and 1 months with daily 2’400mg Echinacea purpurea extract (Echinaforce®, EF). The prevention cycles were interrupted by breaks of 1 week. Acute respiratory symptoms were treated with 4’000 mg EF for up to 10 days, and their severity assessed via a diary. Naso/oropharyngeal swabs and venous blood samples were routinely collected every month and during acute illnesses for detection and identification of respiratory viruses, including SARS-CoV-2 via RT-qPCR and serology. Clinical Trials registration Nr: NCT05002179. Summarized over all phases of prevention, 21 and 29 samples tested positive for any virus in the EF and control group, of which 5 and 14 samples tested SARS-CoV-2 positive (RR=0.37, Chi-square test, p=0.03). Overall, 10 and 14 symptomatic episodes occurred, of which 5 and 8 were Covid-19 (RR=0.70, Chi-square test, p>0.05). EF treatment when applied during acute episodes significantly reduced the overall virus load by at least 2.12 log10 or approx. 99% (t-test, p<0.05), the time to virus clearance by 8.0 days for all viruses (Wilcoxon test, p=0.02) and by 4.8 days for SARS-CoV-2 (p>0.05) in comparison to control. Finally, EF treatment significantly reduced fever days (1 day vs 11 days, Chi-square test, p=0.003) but not the overall symptom severity. There were fewer Covid-19 related hospitalizations in the EF treatment group (N=0 vs N=2). EF exhibited antiviral effects and reduced the risk of viral RTIs, including SARS-CoV-2.